Barreras y facilitadores del sistema de salud relacionadas con el seguimiento de anormalidades citológicas, Medellín-Colombia (2014)
ABSTRACT: Identifying barriers and facilitators of the diagnostic monitoring and treatment of cytological abnormalities in low-income women users of the public health service network in Medellin, Colombia. Methods: We created eight focal groups (62 women) according to age groups (ages 25-45 and 46-69), and performed a content analysis. Results: The reported barriers of the health system were: a) structural barriers: fragmentation in the provision of the service, problems with the affiliations and characteristics of the affiliation regime; b) management barriers: problems and delays in the assignment of appointments, long queues, problems with authorizations and mistreatment; and c) economic barriers derived from the aforementioned and related with expenses. Management and structural facilitators were also mentioned. Conclusion: Some structural characteristics of the health system and the management of insurance companies limit access for women to the monitoring of pre-cancerous lesions.